Film Discourse in the Contemporary World: Semiotics and Analysis - Erkaeva Dilnoza Baxtiyorovna (Universitas Muhammadiyah Sidoarjo, 2022)
The most complete characterization of film discourse as a sign system is given below:1. Film discourse refers simultaneously to optical (perceived by sight) and auditory (perceived by hearing) sign systems. 2. Film discourse is non-biological (cultural) natural semiotics, the occurrence of which is not planned or organized.3. Film discourse refers to complex multi-level semiotics. It has subsystems of signs that form a certain hierarchy. Signs in such semiotics are combined according to certain rules, and changing theorder of the location of one sign we change the meaning of the whole combination of signs. 4. Film discourse is an open semiotics that has the ability to interact with the environment.5. Depending on the approach to research, the units of cinema discourse can be considered the minimum non-discrete image units; large segments (frame, plan), which in addition to the visualcomponent include movement, sound, etc.; chain of frames. 6. Cinema discourse is a multi-code semiotics, which is based on several codes that operatewithin each generating system. There are also codes that control the combination of differentsemiotic systems in the movie and work at their junction, genre emotiveness (drama, comedy,tragedy, thriller, etc.), an artistic chronotope in the form of a temporal perspective of a retrospective(futurological film, historical drama) and localization of events - both fictional and real ones (alienlife and events of an abandoned God of Texas town). The cinema discourse also reflects the ethnocultural specific features of both the creators of the film itself and the habitat, coupled with the socioculturalenvironment of their artistic creations.